Spatial Relationships Between pH and Vegetation Pattern in an Area Contaminated with Heavy Metals - Kovács, Elza; Tamás, János (Acta Agraria Debreceniensis, 2003)
It is not possible to gain information on the risk factor representing the bioavailability and the mobility of the contaminants only on the basis of their total concentrations. Especially, in case of heavy metals, which can be charaterised with very different chemical forms and their mobil and mobilizable parts are determined by complex balances highly sensitive to the changing environmental conditions. Considering mine tailings, however, the toxic elements are basically in ore forms having low adsorption capacity, thus the heavy metal ion concentration in solution is governed mainly by the pH conditions. In Gyöngyösoroszi, the spatial distribution of the total heavy metal concentrations as well as that of pH values determining the bioavailable part of the toxic elements were estimated and by mapping the vegetation pattern, relationship was analysed among the total Zn, Cu, Pb and As concentrations, the pH and the species present. Results show that the presence of the certain plant species is highly determined by the pH on the mine tailing material, the highest vegetation density was found where the bioavailability of the toxic elements were considered the smallest as a result of the neutral pH. As a result, high diversity could be found even in places where the total zinc, copper, lead and arsenic concentrations were extreme. In addition, plant species could be identified, which are tolerant to toxic elements and present even if the pH is low and the bioavailable part of the heavy metals is relatively high.